"More Guts Than Brains?"–The Role of Gut Microbiota in Idiopathic Intracranial Hypertension. Issue 1 (March 2022) - Berkowitz, Eran; Kopelman, Yael; Kadosh, Dana; Carasso, Shaqed; Tiosano, Beatrice; Kesler, Anat; Geva-Zatorsky, Naama
Abstract : Background: Idiopathic intracranial hypertension syndrome (IIH) is most common among obese women. Weight loss is an important factor in improving papilledema. Over the last decade, growing evidence has identified gut microbiota as a potential factor in the pathophysiology of obesity. Accordingly, we investigated whether the gut microbiome is modified in IIH patients compared with healthy controls, and provide possible new treatment venues. Methods: Shotgun metagenomic sequencing of the gut microbiome of 25 cases of IIH patients (according to the modified Dandy criteria) and 20 healthy controls. Participants were further stratified according to their body mass index. The total DNA from each sample was extracted using the PureLink Microbiome DNA Purification Kit A29789 (Invitrogen, Thermo Fisher Scientific, US). Library preparation was performed using the Nextera DNA Flex Library Prep Kit. Samples were sequenced on the Illumina Novaseq 6000 device. A list of bacterial species that significantly differed between the IIH patients and healthy controls was produced in addition to species diversity. In addition, patients' cohort alone was analyzed, (excluding the healthy controls), and the effect of acetazolamide treatment on their gut microbiota was analyzed. Results: IIH patients have a lower diversity of bacterial species compared with healthy individuals. These bacteria, that is, Lactobacillus ruminis (L. ruminis) ( p <6.95E-08), Atopobium parvulum ( p <3.9E-03), Megamonas hypermegale ( p <5.61E-03), Ruminococcus gnavus ( p <1.29E-02), MEL.A1 ( p <3.04E-02), and Streptococcus sp. I-G2 (p<3.04E-02), were previously characterized with beneficial health effects. Moreover, we found that Lactobacillus brevis, a beneficial bacterium as well, is more abundant in acetazolamide treated patients ( p <7.07E-06). Conclusions: Gut microbiota plays a potential role in IIH etiology and therefore, can provide a promising new treatment approach for this disease.